ISGITN Newsletter. (Berlin : International Support Group for Information Transfer and Networking, 1994)
Fonds Suzan Daniel (FSD)
Periodiciteit : tweemaandelijksRedactie : Elberfelderstrasse 25, 10555 Berlin
Engels
Periodiek